De-escalating 'dataveillance' in schools. (December 2022) - Nichols, T. Philip; Monea, Alexander
T. Philip Nichols and Alexander Monea explore the spread of data-driven surveillance (i.e., dataveillance) technologies in schools, which are increasingly used as a strategy for mitigating safety risks. They argue that the sense of security schools derive from these technologies often comes at the cost of students' actual well-being and privacy. Drawing on research with teachers and administrators, they highlight several ethical challenges dataveillance technologies raise as they are incorporated into classrooms. They conclude with suggestions for how educators might de-escalate their dependence on dataveillance without compromising students' safety .